Re-biopsy by endobronchial ultrasound procedures for mutation analysis of non-small cell lung cancer after EGFR tyrosine kinase inhibitor treatment. Issue 1 (December 2016) - Izumo, Takehiro; Matsumoto, Yuji; Chavez, Christine; Tsuchida, Takaaki
Abstract Background Re-biopsy for resistant non-small cell lung cancer (NSCLC) after treatment with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) is important for selection of better therapy, but there have been no reports about the utility of endobronchial ultrasound (EBUS)-guided procedures for such purpose. The aim of this study was to evaluate the utility of EBUS-guided re-biopsy for resistant NSCLC after treatment with EGFR-TKIs. Methods From January 2013 to December 2015, 53 consecutive patients who underwent EBUS-guided re-biopsy for mutation analysis of NSCLC after EGFR-TKI treatment were assessed. Results Nine patients underwent EBUS-guided transbronchial needle aspiration (EBUS-TBNA) and 44 patients underwent EBUS with a guide sheath (EBUS-GS) transbronchial biopsy. The technical success rates were 100 %. As for mutation analysis, all 9 specimens (100 %) from EBUS-TBNA and 33 specimens (75.0 %) from EBUS-GS were adequate for gene profiling. The remaining 11 specimens from EBUS-GS procedures were inadequate for mutation analysis owing to the absence of tumor component in the sample (n  = 6) or insufficient specimen (n  = 5). There were no related severe complications. Conclusions Re-biopsy by both EBUS-TBNA and EBUS-GS were useful and safe sampling procedures for mutation analysis of EGFR-TKI resistant NSCLC.